(untitled) (International Journal of Innovative Research in Computer Science & Technology, 2021)
9.4 million trees across forest areas in India have been lost to development projects over the period of past 4 years (2015-16 to 2018-19). This is according to the Union ministry of environment, forests and climate change (MoEFCC). Afforestation refers to the effort to plant trees in barren lands to create a forest. Planting trees, sowing seeds in a barren land so as to create a forest. It is very vital as it helps to keep in check the over usage of natural resources by providing an alternative source. Planting trees is always beneficial to the environment regardless of the habitat.